The social value of urban design in mixed use developments in London - Alzahrani, Abdulaziz (2017)
This thesis investigates the United Kingdom (UK) government’s influence on the quality of urban design through the role of mixed-use developments. The Urban Task Force (UTF), the Commission for Architecture and the Built Environment (CABE), the Department of the Environment, Transport and the Regions (DETR) and others have influenced and shaped development decisions by setting up broad recognition of the value of urban design and quality regeneration of private and public sectors. The thesis is an in-depth analysis of two inner-city mixed-use housing developments with publicly accessible spaces that exemplify this trend in valuing spaces that are available to the public in response to the drive for regeneration and to counter social exclusion. Empire Square and Bermondsey Square illustrate an interesting model of public/private partnership to provide public spaces that might be applicable elsewhere. These developments also have an effect on issues of control and management which has an impact on the performance of these spaces in our cities. The thesis explored this model of creating urban public spaces through the perspective of the user’s perception and sought to identify its perceived value regarding use, identify, social coherence and others. The work followed a case study approach and employed mixed methods. An extensive review of the literature helped to establish the criteria of analysis of case studies, social value and place making; this was to understand both the patterns of spatial constructions of individuals’ actions and perceptions and the social life of publicly accessible spaces. In the two case studies combined, participants at the squares completed a total of a hundred surveys and thirty-three semi-structured interviews; additionally, many site observations were conducted at different times of the day to track human movement, activities, spatial qualities, social interactions and spatial interrelations. The research has shown that, from the user’s perspective, these parameters of social value are linked to vitality, the provision of events and activities, improving the supply of amenities, accessibility, control and the image. The findings demonstrated that, while both projects conform to the generic description of a good placemaking as defined by UTF, CABE, and others, non-tangible and programmatic performances override the perceived quality of aesthetic and form in the delivery of successful places. The outcomes showed how objectives and principles of urban design are abstract and must be articulated by more detailed guidelines in terms of intangible and non-physical benefits for them to be beneficial for public places and to have an impact on people’s lives. The balance between aesthetic aspects and activities and functions that enable and boost social value should occur in places that spread all over our cities. This research suggested that placemaking adds value by balancing the generation of space and behavioural settings to deliver social benefits to our communities.